Melatonin ameliorates manganese-induced neurological deficits in mice by inhibiting TXNIP signaling–mediated neuroinflammation and microglial pyroptosis: Role of SIRT6 - Jia Liu; Jixing Liang; Keyu Chen; Kuan Liu; Changjiang Yu; Zhuo Ma; Bin Xu (Journal of Hazardous Materials, 2026)

Effect of arsenic-contaminated irrigation water exposeure combined with conventional and biodegradable microplastics on arsenic fractionation in the paddy soil - Haotian Yu; Fan Wu; Feng Peng; Keyu Long; Yihui Wei; Teng Ma (Environmental Pollution, 2026)

From built-in LiDFP to high-stability interface: A targeted and persistent multistage strategy for lithium-rich cathode - Jin Zhu; Xiaosong Zhang; Denghui Ma; Lei Zhang; Yiyao Xiao; Keyu Zheng; Jiamin Duan; Shunjie Xu; Longhao Cao; Yinghui Li; Guanghua Guo; Xiuxia Zuo; et al. (Chemical Engineering Journal, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Comprehensive chemical molecular characterization of petroleum-contaminated soils: Unraveling physical migration and biotransformation processes in the vadose and saturated zones - Wang Yu; Yuruo Wan; Jiuhao Song; Keyu Duan; Junjie Guan; Qi Gao; Yuping Zhang; Jianhui Ma; Jie Ma (Environmental Pollution, 2026)

Ionic liquid-mediated concurrent oxygen vacancies and N-doped carbon in hierarchical TiP2O7 for lithium storage - Wenfang Cui; Yongmei Sun; KeYu Zhang; Chengcheng Shi; Peng Fu; Mei Ma (Chemical Engineering Journal, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

Synergistic pathways for regional energy transition and water conservation: insights from the receiving areas of the South-to-North Water Diversion Middle Route - Weiwen Liu; Chao Ma; Haixing Gou; Ximeng Xu; Ruixin Zhang; Weiren Huang; Keyu Guo (Journal of Hydrology, 2026)

ACSL4 Inhibition by AS-252424 Protects Visual Function by Suppressing RGC Ferroptosis After Retinal Ischemia Reperfusion Injury - Keyu Liu; Zihao Lin; Wu Xiang; Jiayi Zhang; Xiaofeng Wu; Chenzhao Ma; Yantao Wei; Jiawei Wang; Jianqiao Li (Molecular Neurobiology, 2026)

Deciphering gut microbial dynamics and multi-omics changes in yogurt-based dietary interventions - Qiuwen He; Yaru Sun; Hao Jin; Lai-Yu Kwok; Teng Ma; Keyu Quan; Yalin Li; Xuan Shi; Zhihong Sun; Heping Zhang (Science Bulletin, 2025)

Surfactants facilitate microbial growth on the surface of microplastics in biological wastewater treatment - Feiyuan Liu; Keyu Ma; Huan He; Xing Wan; Ziwei Guo; Jingye Cui; Wanqi Shi; Bin Huang; Xuejun Pan (Journal of Environmental Management, 2025)

Delayed progression of diabetic cataractogenesis and retinopathy by topical administration of highly biocompatible carbon dots derived from Scutellaria barbata and Herba hedyotis diffusae - Jiawei Wang; Yihan Zhao; Xueying Yang; Can Li; Keyu Liu; Chenzhao Ma; Yanyan Jiang; Jianqiao Li (Chemical Engineering Journal, 2025)

Architectural design of multidimensional carbonaceous structures: Synergistic pathways enabling high-energy silicon-based anodes - Wendi Chen; Lingjun Guo; Ruonan Zhang; Guangyao Liu; Yue Ma; Dian Jia; Hejun Li; Keyu Xie (Chemical Engineering Journal, 2025)

Synergy in the transformation of Bisphenol A by anaerobic microorganisms and manganese dioxide: The bridging role of extracellular polymeric substances - Feiyuan Liu; Zhicheng Liao; Huan He; Keyu Ma; Weiqing Ma; Weiwei Ren; Bin Huang; Hongwen Sun; Xuejun Pan (Bioresource Technology, 2025)

Fingerprinting complex mixed oil spills at refineries: Source identification, quantitative source apportionment, and biodegradation assessment - Wang Yu; Jiayi An; Jiuhao Song; Junjie Guan; Keyu Duan; Wei Zhou; Liting Tian; Jie Ma (Water Research, 2025)

PRKAG1 mediates the anti-Japanese encephalitis virus effect of Nitazoxanide through autophagy - Hui Ma; Xiaoyang Wang; Chunmei Wang; Wenchong Ye; Wen Zhou; Fengcai Zou; Keyu Zhang (Veterinary Microbiology, 2025)

Paleoenvironment and organic matter enrichment in the Kaijiang–Liangping Trough across the Emeishan Large Igneous Province (ELIP) - Mengxiang Yu; Jianhua Zhao; Keyu Liu; Qinhong Hu; Wei Wu; Quanyou Liu; Chao Luo; Yang Chen; Hongyu Ma; Zhijun Jin (Marine and Petroleum Geology, 2025)

Dynamic interactions in energy-water nexus: risk-based framework for balancing electricity expansion and water resource sustainability - Haixing Gou; Chao Ma; Ximeng Xu; Weiwen Liu; Ruixin Zhang; Weiren Huang; Keyu Guo (Journal of Hydrology, 2025)

The synergistic effect of triazine-N and secondary amine-N anchors iodine species with MXene composite cathode for stable aqueous Zn–I2 battery - Jing Ma; Yaoyao Linghu; Kai Yuan; Rui Zhou; Hui Gao; Peihua Zhao; Shaohui Guo; Huiqi Wang; Yongping Qu; Chao Shen; Keyu Xie (Chemical Engineering Journal, 2025)

Excessive mitochondrial stress response triggers neuronal injury through the persistent eIF2α phosphorylation in mice exposed to manganese - Yunfei Jia; Bin He; Keyu Chen; Kuan Liu; Changjiang Yu; Bo Sun; Zhuo Ma; Bin Xu (Journal of Hazardous Materials, 2025)

Cobalt-doped covalent organic framework effectively enhances Fenton-like activity: radical and non-radical dual pathways enhancement - Yunchao Ma; Chuanxue You; Yuxin Yao; Shengnan Qi; Tianyu Zhou; Wei Jiang; Keyu Cui; Bo Hu; Linlin Liu (Chemical Engineering Journal, 2025)

Impact of Proton Pump Inhibitors on Osimertinib-Induced Cardiotoxicity in NSCLC Patients - Haitao Wang; Sinan Ma; Weijia Huang; Keyu Chen; Jiao Xie; Na Wang; Youjia Li; Qianting Yang; Xin Yang; Yan Wang (Cardiovascular Toxicology, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

How bedding-parallel fractures affect fluid activity in a relatively closed lacustrine shales system: Evidence from calcite veins - Zilong Li; Kelai Xi; Xiaobing Niu; Xiujuan Wang; Wenzhong Ma; Xiao Hui; Jiangyan Liu; Changyu Fan; Miruo Lin; Keyu Liu; Yingchang Cao (Marine and Petroleum Geology, 2025)

Disentangling and interpreting nonlinear molecular and isotopic variations in petroleum using machine learning - Keyu Tao; Jian Cao; Yuce Wang; Wanyun Ma (Marine and Petroleum Geology, 2025)

The impact of organic matter and iron/calcium coupling on phosphorus retention in the hyporheic zone of the Danjiangkou area tributary: Evidence from bonding recognition - Yu Chen; Teng Ma; Liuzhu Chen; Jiabao Sun; Keyu Long; Gongyu Zhou; Weidong Sun (Science of The Total Environment, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Degradation of Bisphenol A by manganese minerals: The impact of inorganic and organic ligands - Huan He; Feiyuan Liu; Zhicheng Liao; Min Shi; Keyu Ma; Shanshan Yang; Bin Huang; Xuejun Pan (Journal of Environmental Chemical Engineering, 2024)

Optimal design of transverse dampers incorporating inherent stiffness effects for stay cable vibration control: A case study with wire rope dampers - Keyu Lai; Wei Fan; Zhengqing Chen; Huawei Niu; Lingfei Ma; Shouying Li (Engineering Structures, 2024)

Germ cell-specific gene 2 accelerates cell cycle in epithelial ovarian cancer by inhibiting GSK3α-p27 cascade - Keyu Zhu; Xiaolu Ma; Xiaolin Guan; Ying Tong; Suhong Xie; Yanchun Wang; Hui Zheng; Lin Guo; Renquan Lu (Journal of Molecular Histology, 2024)
Epithelial ovarian cancer (EOC) is one of the most common malignant gynecological tumors with rapid growth potential and poor prognosis, however, the molecular mechanism underlying its outgrowth remained elusive. Germ cell-specific gene 2 (GSG2) was previously reported to be highly expressed in ovarian cancer and was essential for the growth of EOC. In this study, GSG2-knockdown cells and GSG2-overexpress cells were established through lentivirus-mediated transfection with Human ovarian cancer cells HO8910 and SKOV3. Knockdown of GSG2 inhibited cell proliferation and induced G2/M phase arrest in EOC. Interestingly, the expression of p27, a well-known regulator of the cell cycle showed a most significant increase after GSG2 knockdown. Further phosphorylation-protein array demonstrated the phosphorylation of GSK3αSer21 decreased in GSG2-knockdown cells to the most extent. Notably, inhibiting GSK3α activity effectively rescued GSG2 knockdown’s suppression on cell cycle as well as p27 expression in EOC. Our study substantiates that GSG2 is able to phosphorylate GSK3α at Ser21 and then leads to the reduction of p27 expression, resulting in cell cycle acceleration and cell proliferation promotion. Thus, GSG2 may have the potential to become a promising target in EOC.

Effect of hydrothermal carbonization on pyrolysis behavior, nutrients and metal species distribution in municipal sludge - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Zhilin Xie; Tianqin Zhang; Jin Wang (Bioresource Technology, 2024)

Integration of hydrothermal liquefied sludge as wastewater for anaerobic treatment and energy recovery: Aqueous phase characterization, anaerobic digestion performance and energy balance analysis - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Pengcheng Zhao; Manyi Yang; Jin Wang (Journal of Water Process Engineering, 2024)

Ibuprofen inhibits anaplastic thyroid cells in vivo and in vitro by triggering NLRP3-ASC-GSDMD-dependent pyroptosis - Haohao Guo; Runsheng Ma; Yifei Zhang; Keyu Yin; Gongbo Du; Fanxiang Yin; Hongqiang Li; Ziyang Wang; Detao Yin (Inflammopharmacology, 2024)
Pyroptosis is a novel type of proinflammatory programmed cell death that is associated with inflammation, immunity, and cancer. Anaplastic thyroid carcinoma (ATC) has a high fatality rate, and there is no effective or standard treatment. The disease progresses rapidly and these tumors can invade the trachea and esophagus, leading to breathing and swallowing difficulties. Hence, new treatment methods are greatly needed. Ibuprofen is a common drug that can exert antitumor effects in some cancers. In this study, we demonstrated in vitro and in vivo that ibuprofen can induce ATC pyroptosis. Hence, we treated C643 and OCUT-2C ATC cells with ibuprofen and found that several dying cells presented the characteristic morphological features of pyroptosis, such as bubble-like swelling and membrane rupture, accompanied by activation of ASC and NLRP3 and cleavage of GSDMD. Along with the increased release of LDH, ibuprofen treatment promoted apoptosis and inhibited viability, invasion, and migration. However, overexpression of GSDMD significantly inhibited ibuprofen-induced pyroptosis. In vivo, research has demonstrated that thyroid tumor growth in nude mice can be suppressed by ibuprofen-induced pyroptosis in a dose-dependent manner. In this research, we explored a new mechanism by which ibuprofen inhibits ATC growth and progression and highlighted its promise as a therapeutic agent for ATC.

Selective efficient photocatalytic degradation of antibiotics and direct Z-type migration pathway for hierarchical core–shell TiO2/g-C3N4 composites - Hu Liu; Jianmei Pan; Keyu E; Yi Guan; Wenbo Gou; Peng Wang; Shahid Hussain; Ze Du; Chengfei Ma (Environmental Science and Pollution Research, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

Revealing continuous hydrocarbon generation and shale oil accumulation of saline lacustrine source rocks by sequential extraction - Wenwen Li; Jian Cao; Wenxuan Hu; Yong Tang; Baoli Xiang; Wanyun Ma; Wenjun He; Keyu Tao; Yingqi Wang (Fuel, 2023)

Discovery of a heterotrophic aerobic denitrification Pseudomonas sp. G16 and its unconventional nitrogen metabolic pathway - Yu Gao; Junwen Zhu; Keyu Wang; Yong Ma; Jun Fang; Gang Liu (Bioresource Technology, 2023)

Targeting gut microbiota and metabolism as the major probiotic mechanism - An evidence-based review - Teng Ma; Xin Shen; Xuan Shi; Hafiz Arbab Sakandar; Keyu Quan; Yalin Li; Hao Jin; Lai-Yu Kwok; Heping Zhang; Zhihong Sun (Trends in Food Science & Technology, 2023)

Differential evolution of extracted bitumen and solid bitumen in a hybrid shale system - Weijiao Ma; Yingchang Cao; Kelai Xi; Keyu Liu; Jinzhong Liu (Organic Geochemistry, 2023)

The influence of CO2 partial pressure on the stability of dawsonite-based on water-rock physical experiment and numerical simulation - Fulai Li; Chun Zhang; Kaining Wang; Wenkuan Ma; Jianlei Yang; Qizhen Du; Shaogui Deng; Keyu Liu (Applied Geochemistry, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

Creating aligned porous structure with cobweb-like cellulose nanofibrils in MXene composite aerogel for solar-thermal desalination and humidity response - Mingqi Ding; Wenjie Ma; Pengju Liu; Jingbo Yang; Keyu Lan; Dawei Xu (Chemical Engineering Journal, 2023)

Revisiting Rhenium-Osmium Isotopic Investigations of Petroleum Systems: From Geochemical Behaviours to Geological Interpretations - Shao-Jie Li; Xuan-Ce Wang; Simon A. Wilde; Zhuyin Chu; Chaofeng Li; Sheng He; Keyu Liu; Xingzhi Ma; Yuxiang Zhang (Journal of Earth Science, 2021)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)